2020
DOI: 10.1111/anae.15292
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative evaluation of aerosol generation during tracheal intubation and extubation

Abstract: Summary The potential aerosolised transmission of severe acute respiratory syndrome coronavirus‐2 is of global concern. Airborne precaution personal protective equipment and preventative measures are universally mandated for medical procedures deemed to be aerosol generating. The implementation of these measures is having a huge impact on healthcare provision. There is currently a lack of quantitative evidence on the number and size of airborne particles produced during aerosol‐generating procedures… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
221
2
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(238 citation statements)
references
References 19 publications
13
221
2
2
Order By: Relevance
“…Dhillon et al [6] report their findings in cm -3 and, for the purpose of this editorial, we have converted their data to l -1 to allow direct comparison with Brown et al [7]. Both groups 3 The difference in sampling locations between these two studies: we still have a poor understanding of the temporal and spatial dispersion of aerosols from tracheal intubation and aerosol measurement results are likely to be time-and location-dependent based on these two studies.…”
Section: -1776)mentioning
confidence: 98%
See 1 more Smart Citation
“…Dhillon et al [6] report their findings in cm -3 and, for the purpose of this editorial, we have converted their data to l -1 to allow direct comparison with Brown et al [7]. Both groups 3 The difference in sampling locations between these two studies: we still have a poor understanding of the temporal and spatial dispersion of aerosols from tracheal intubation and aerosol measurement results are likely to be time-and location-dependent based on these two studies.…”
Section: -1776)mentioning
confidence: 98%
“…Whether or not these pose a clinically significant risk depends on the number, size and concentration of infectious aerosols [5]. In this issue of Anaesthesia, there are two papers using robust scientific approaches to evaluate aerosol generation during tracheal intubation and extubation to address this gap in evidence [6,7]. From these two studies, it can be confirmed that tracheal intubation and extubation does produce a certain number of aerosols which can remain suspended and spread in the operation room air; but does this research provide any reassurance as to whether what we are currently doing is safe or appropriate?…”
Section: -1776)mentioning
confidence: 99%
“…An observational study has confirmed that the risk of the spread of viral droplets and aerosols is minimum during induction of anesthesia and during tracheal intubation [32]. This study, in which aerosol concentrations near the patient's mouth were measured, has shown that aerosol level was minimum during induction of anesthesia and tracheal intubation, which was 500-fold less than the average concentration recorded during coughing.…”
Section: When To Use?mentioning
confidence: 60%
“…This study, in which aerosol concentrations near the patient's mouth were measured, has shown that aerosol level was minimum during induction of anesthesia and tracheal intubation, which was 500-fold less than the average concentration recorded during coughing. In contrast, aerosol concentration was increased markedly during emergence from anesthesia, and the concentration was 15-fold greater than that seen during tracheal intubation [32]. From these results, it is reasonable to conclude that an aerosol containment device has a much less use during induction of anesthesia than during emergence from anesthesia.…”
Section: When To Use?mentioning
confidence: 76%
“…Recommendations for the personal protective equipment (PPE) required during aerosol-generating procedures (AGPs), such as advanced airway management, are inconsistent amongst different countries and regions. 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 Two new studies report conflicting results, either supporting 9 or opposing 10 tracheal intubation and extubation as AGPs. Both studies were limited by small sample size, and used different definitions of AGPs and particle detection methods.…”
Section: Personal Protective Equipmentmentioning
confidence: 99%